Sporting activity does not fully prevent bone demineralization at the impaired hip in athletes with amputation - Cavedon, Valentina; Sandri, Marco; Peluso, Ilaria; Zancanaro, Carlo; Milanese, Chiara (Frontiers in Physiology, 2022)
There is lack of information about bone mineralization at the lumbar spine and bilateral hips of athletes with unilateral lower limb amputation. The present study assessed for the first time the areal bone mineral density at the lumbar spine and at the hip of the able and impaired leg by means of Dual-Energy X-Ray Absorptiometry using a large sample (N = 40) of male athletes. Results showed that bone demineralization in athletes with unilateral lower limb amputation is found at the impaired hip but not at the lumbar spine and may therefore be site-specific. The extent of hip demineralization was influenced by the level of amputation, with about 80% of athletes with above knee amputation and 10% of athletes with below knee amputation showing areal bone mineral density below the expected range for age. Nevertheless, a reduced percentage of fat mass and a lower fat-to-lean mass ratio in the residual impaired leg as well as a greater amount of weekly training was positively associated with bone mineralization at the impaired hip (partial correlation coefficients = 0.377-0.525, P = 0.040-0.003). Results showed that participation in adapted sport has a positive effect on bone health in athletes with unilateral lower limb amputation but is not sufficient to maintain adequate levels of bone mineralization at the impaired hip in athletes with above-knee amputation. Accordingly, physical conditioners should consider implementing sporting programs, according to the severity of the impairment, aimed at improving bone mineralization at the impaired hip and improve body composition in the residual impaired leg.